(untitled) (Journal of Asian Development Studies, 2024)
he present study explores the interrelationships between social-emotional competence, work-life balance, and sleep quality among medical students. Thestudy is critical because it explores the depressing factors of medical students. This research was conducted on samples of 200 Faisalabad medical university and independent medical university students. Using a cross-sectional design, data were collected via self-report questionnaires, including the social-emotional competence scale, the work-life balance scale, and the Pittsburgh sleep quality index (PSQI). Various statistical analyses, such as descriptive statistics, correlation analysis, and regression modelling, were used to analyze the data. The results revealed significant correlations between the variables, indicating that higher socio-emotional competence was associated with better work-life balance and sleep quality. Findings highlight the importance of developing targeted interventions to enhance social-emotional skills, promote work-life balance, and improve sleep hygiene among medical students. This study contributes to the growing body of literature on medical student well-being and provides actionable insights for creating more balanced and supportive learning environments for medicalinstitutions